Steel annealing method

By controlling the humidity of the calcining atmosphere during the steel heat treatment process, the problem of difficult control of the thickness of the decarbonized layer is solved, and the dual optimization of the mechanical properties of steel and the embrittlement (LME) resistance of liquid metal brittleness is achieved, which is suitable for the needs of high-performance steels in automobile manufacturing.

JP7656632B2Active Publication Date: 2025-04-03ARCELORMITTAL SA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022567266
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-05-07
Filing Date
2021-04-22
Publication Date
2025-04-03
Estimated Expiration
2041-04-22

AI Technical Summary

Technical Problem

Although the decarbonized layer formed by existing high-strength steel during the manufacturing process improves the brittle embrittlement (LME) resistance of liquid metal, its thickness is difficult to control, resulting in a decline in the mechanical properties of the steel.

Method used

By controlling the humidity of the calcining atmosphere during the heat treatment of the steel, especially by using higher humidity in the heating stage and lower humidity in the maintenance stage, the thickness of the decarbonized layer of the steel surface is controlled, so as to optimize the mechanical properties and LME resistance of the steel.

Benefits of technology

The dual optimization of the mechanical properties of steel and LME resistance is achieved, ensuring high performance and durability of steel when used in automobile manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656632000004
    Figure 0007656632000004
  • Figure 0007656632000005
    Figure 0007656632000005
  • Figure 0007656632000006
    Figure 0007656632000006
Patent Text Reader

Abstract

The present invention relates to a method for producing a steel strip, a steel strip with controlled decarburization depth, a spot welded joint, and uses of said steel strip or said spot welded joint. The invention is suitable for the automotive industry due to its improved resistance to liquid metal embrittlement (LME) together with targeted mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for manufacturing a steel strip, a spot welded joint, and uses of said steel strip or said spot welded joint. The present invention is particularly suitable for the automotive industry due to the improved liquid metal embrittlement (LME) resistance properties of advanced high strength steels. [Background technology]

[0002] High strength steels are used in the automotive industry, especially for structural components, to reduce the weight of cars. Such steel grades contain alloying elements to significantly improve their mechanical properties.

[0003] During their manufacture and before coating, full hardened steels undergo an annealing process that enhances their strength-ductility balance, in which the steel is heated and maintained above its recrystallization temperature in a controlled atmosphere and then cooled to the galvanizing temperature for galvanizing of the steel surface by the hot dip galvanizing process.

[0004] For example, a common practice is to heat full hard steel from ambient temperature to its recrystallization temperature (heating step) and then hold this temperature (soaking step). Both steps are carried out in an atmosphere containing, for example, 5% by volume H2 together with 95% N2 and having a dew point above -20°C. The steel is then rapidly cooled to the desired temperature.

[0005] In the heating and soaking zone at around 700°C, the dew point is controlled so that oxygen present in the high dew point atmosphere in the furnace diffuses to the sub-surface layer of the steel at a faster rate than the diffusion of oxide-forming steel alloying elements, such as manganese (Mn), aluminum (Al), silicon (Si) or chromium (Cr), to the steel surface.

[0006] The presence of C together with other steel alloying elements that form oxides, such as Mn, Si, Cr and Al, results in at least two reactions.

[0007] First, as shown in Fig. 1, oxygen reacts with carbon to form gases such as CO2 and CO (Images A and B), causing the carbon atoms in the subsurface layer of the steel to deplete and a decarburized layer 1 (Images C and D) to form. The carbon depletion becomes stronger closer to the surface 2. In addition to the above, carbon atoms diffuse from the bulk 3 into the carbon depletion zone 1 (Image E). All these phenomena occur simultaneously (Image F). When more carbon atoms leave the subsurface layer of the steel than diffuse into the layer, the subsurface layer of the steel becomes decarburized and / or forms a carbon depletion region compared to the carbon level of the bulk steel.

[0008] Second, as shown in Fig. 2, oxygen reacts with steel alloying elements such as manganese (Mn), aluminum (Al), silicon (Si), and chromium (Cr), which have a higher affinity for oxygen than iron, to form oxides mainly on the steel surface, known as internal selected oxides reported as 4, and only a small amount of oxides on the surface known as external selected oxides reported as 5. These oxides are, for example, elemental oxides such as MnO and SiO2. Furthermore, it forms complex mixed oxides such as MnSiO3 and MnSiO4. These oxides can exist in the form of discontinuous small lumps or as a continuous layer along the grain boundaries of the subsurface layer of the steel. These internal oxides mainly exist along the grain boundaries and also within the grains.

[0009] In subsequent processing steps, these steels are usually coated with another metal or metal alloy such as a zinc-based coating to improve properties such as corrosion resistance and phosphatability. This metal coating can be deposited by a hot-dip coating method or an electroplating method. The zinc-based coating, also known as hot-dip galvanized coating, usually contains about 0.1 - 0.4 wt% aluminum. The aluminum reacts preferentially with iron to form a barrier layer between the steel / coating interface. This barrier layer is mainly composed of Fe and Al and is an intermetallic compound Fe2Al 5-x Zn x (0 < x < 1) is formed. The barrier layer may contain some Zn atoms.

[0010] When used in the automotive industry, galvanized steel sheets are usually welded together by the resistance spot welding (RSW) method. During this process, liquid zinc or liquid zinc alloys penetrate into the sub-surface layer area of ​​the steel, causing liquid metal embrittlement (LME) of the steel, which leads to a decrease in the ductility of the steel and causes premature failure. Summary of the Invention [Problem to be solved by the invention]

[0011] Regarding the decarburization layer, the thicker the decarburization layer, the better the resistance to LME. However, the decarburization layer degrades the mechanical properties of the steel. It is mainly due to the formation of soft ferrite phase in the steel sub-surface region. The thickness of the decarburization layer must be controlled to satisfy the target mechanical properties and provide good LME resistance properties. Overall, the annealing atmosphere needs to be controlled to generate an optimal depth of the decarburization layer that satisfies both the target mechanical properties as well as good LME resistance. The object of the present invention is to provide a solution to solve the above problem. [Means for solving the problem]

[0012] This object is achieved by providing a method according to claim 1. The method may also include the features of any of claims 2 to 9. This object is also achieved by providing a steel plate according to claims 10 to 13 and a spot welded joint according to claim 14. This object is also achieved by providing preferred uses for the claimed steel plate or spot welded joint.

[0013] Other features and advantages of the present invention will become apparent from the following detailed description of the invention.

[0014] To illustrate the invention, various embodiments and non-limiting example testing examples are described with particular reference to the following figures: [Brief description of the drawings]

[0015] [Figure 1] Figure 1 shows the various reactions that take place in an annealing furnace. [Diagram 2] FIG. 2 shows the internal and external oxidation of steel alloying elements. [Diagram 3] 1 shows an embodiment of an annealing furnace and a hot dip plating facility. [Figure 4] 2 shows a second embodiment of the annealing furnace and hot dip plating equipment. [Diagram 5] 1 illustrates an embodiment of an annealing cycle according to the present invention. [Figure 6] 2 shows a second embodiment of an annealing cycle according to the invention. [Figure 7] 1 shows a first embodiment of the claimed steel sheet having a galvanized coating. [Figure 8] 2 shows a second embodiment of the claimed steel sheet having a galvannealed coating. [Figure 9] FIG. 2 shows two SEM images illustrating the effect of the claimed method on the decarbonized layer on a first steel type (Experiments A1 and A2*). [Figure 10] 2 shows two SEM images illustrating the effect of the claimed method on the inner oxide, the inhibition layer and the galvanized coating on a first steel type [Experiment A1 (left image) and Experiment A2* (right image)]. [Figure 11] Two SEM images are shown showing the effect of the claimed method on the decarbonized layer (left image) and on the inner oxide, inhibition layer and galvanized coating (right image) on a second steel type (experiment B1*). [Figure 12] Two SEM images are shown illustrating the effect of the claimed method on the decarburized layer (left image) and on the internal oxide and galvannealed coating (right image) of a first steel type (experiment A3*). [Figure 13] 1 shows SEM images illustrating the effect of the claimed method on the decarburized layer (left image) and on the internal oxide and galvannealed coating (right image) on a second steel (Experiment B2*). [Figure 14] The resistance spot welding technique for a three-ply stack is shown, indicating the possible locations of LME crack formation. [Figure 15]FIG. 1 illustrates an embodiment of a resistance spot welding test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present invention relates to a method for producing coated steel sheet coated with a zinc-based or aluminum-based coating, comprising: A) has the following chemical composition in weight percent: 0.01≦Al≦1.0%, 0.07≦C≦0.50%, 0.3≦Mn≦5.0%, V<0.2%, 0.01≦Si≦2.45%, 0.35≦Si+Al≦3.5, N≦0.01%, P<0.02%, S≦0.01%, Optionally, in weight percent, at least one of the following elements: B≦0.004%, Co≦0.1%, 0.001≦Cr≦1.00%, Cu≦0.5%, 0.0001≦Mo≦0.5%, Nb≦0.1%, Ni≦1.0%, Ti≦0.1%, The preparation of steel sheets, the remainder of whose composition is iron and inevitable impurities resulting from refining; B) Annealing of said steel sheet, which comprises, in this order: i) a preheating step of heating the steel sheet from room temperature to a temperature T1 between 550°C and Ac1+50°C; ii) a heating step of heating the steel sheet in an atmosphere A1 containing between 0.1 and 15% by volume of H2, with the remainder being composed of inert gases, H2O, O2 and unavoidable impurities, and having a dew point DP1 between -10°C and +30°C, from a temperature T1 to a recrystallization temperature T2 between 720°C and 1000°C; iii) a soaking step of holding the steel sheet at the recrystallization temperature T2 in an atmosphere A2 containing between 0.1 and 15% by volume of H2, with the remainder being composed of inert gases, H2O, O2 and unavoidable impurities, and having a dew point DP2 between -30°C and 0°C, the dew point DP1 being higher than the dew point DP2; iv) Cooling process C) Coating the sheet with a zinc-based or aluminium-based coating.

[0017] The following paragraphs discuss and explain the scope of the claimed invention.

[0018] The provided steel has the claimed composition for the following reasons.

[0019] - 0.01≦Al≦1.0 wt% Al increases the Ms temperature, thus destabilizing the retained austenite, and if the Al content exceeds 1.0%, the Ac3 temperature increases, making industrial production difficult.

[0020] - 0.07≦C≦0.50 wt.%: If the carbon content is less than 0.07%, there is a risk of insufficient tensile strength. Furthermore, if the steel microstructure contains residual austenite, it will not be able to achieve the necessary stability to achieve sufficient elongation. If the C content exceeds 0.5%, the hardening of the weld increases.

[0021] - 0.3 ≦ Mn ≦ 5.0 wt.%. Manganese is a solid solution hardening element that contributes to obtaining high tensile strength. However, if the Mn content exceeds 5.0%, it may cause the formation of a structure with excessively marked segregation, which may adversely affect the mechanical properties of the weld. Preferably, the manganese content is in the range between 1.5 and 3.0 wt.%. This allows a satisfactory mechanical strength to be obtained without increasing the difficulty of industrial production of the steel and without increasing the hardenability of the weld.

[0022] - V<0.2% by weight. Vanadium forms precipitates which achieve hardening and strengthening.

[0023] - 0.01≦Si≦2.45wt%. Silicon retards the formation of carbides and stabilizes austenite. When the silicon content exceeds 2.45%, the plasticity and toughness of the steel are significantly reduced.

[0024] The steel may optionally contain elements such as Nb, B, Ni, Ti, Cu, Mo and / or Co for the following reasons:

[0025] Boron may optionally be included in the steel at a content up to 0.004% by weight. By segregating to the grain boundaries, B is beneficial in lowering the grain boundary energy and thus increasing the resistance to liquid metal embrittlement.

[0026] Chromium may be present in a content up to 1.00% by weight. Chromium retards the formation of proeutectoid ferrite during the cooling step after the maximum temperature hold in the annealing cycle, making it possible to achieve higher strength levels. Its content is limited to 1.00% by weight for cost reasons and to prevent excessive hardening.

[0027] Copper may be present in a content up to 0.5% by weight to harden the steel by precipitation of copper metal.

[0028] Molybdenum in amounts up to 0.5% by weight is effective in increasing hardenability and stabilizing retained austenite, since this element retards the decomposition of austenite.

[0029] Nickel may optionally be included in the steel in amounts up to 1.0% by weight to improve toughness.

[0030] Titanium and niobium are also elements which may optionally be used to achieve hardening and strengthening by forming precipitates, but Nb amounts above 0.1% and / or Ti contents above 0.1 wt.% run the risk of excessive precipitation causing a decrease in toughness and must be avoided.

[0031] P and S are considered residual elements resulting from steelmaking. P may be present in amounts up to 0.04 wt.%. S may be present in amounts up to 0.01 wt.%.

[0032] It is preferred that the steel chemistry does not contain Bismuth (Bi), and indeed, without wishing to be bound by any theory, it is believed that the inclusion of Bi in the steel sheet reduces the wettability and therefore the coating adhesion.

[0033] In order to properly understand the disclosed invention, several terms are defined. The dew point is the temperature to which air must be cooled in order to be saturated with water vapor. In steelmaking, Ac1 corresponds to the temperature at which austenite begins to form during heating. Ms corresponds to the temperature at which austenite begins to form martensite during rapid cooling.

[0034] Some steps of the method may be carried out in a furnace as shown in Figure 3 or Figure 4. Both furnaces comprise a preheating section 6, a heating section 7, a soaking section 8, and a cooling section 9. The furnace shown in Figure 4 also includes a carbon partitioning section 10.

[0035] The preheating step is generally carried out after cold rolling the steel to what is also known as the full hard condition. During this preheating, the steel sheet is heated in a non-oxidizing atmosphere from room temperature to a temperature T1 between 550 ° C and Ac1 + 50 ° C. The preheating step can be carried out with any heating means that allows heating the steel at a temperature T1 without producing iron oxide or with limited amounts of iron oxide. For example, this step can be carried out in an RTF (radiant tube furnace) with an atmosphere composed of N2, H2 and unavoidable impurities, in heating by induction means or in a DFF (direct-fired furnace) with an atmosphere with an air / combustible gas ratio less than 1. However, in a DFF composed of several zones, for example 5 zones, it is possible to have an air / combustible gas ratio greater than 1 in the last zone or in the last two zones.

[0036] During the heating process, the steel sheet is heated from a temperature T1 to a recrystallization temperature T2 between 720°C and 1000°C in an atmosphere A1 containing between 0.1 and 15% by volume of H2, the remainder being composed of inert gases, H2O, O2 and unavoidable impurities, and having a dew point DP1 between -10°C and +30°C. Nitrogen can be used as the inert gas.

[0037] During the soaking process, the steel sheet is heated at the recrystallization temperature T2 in an atmosphere A2 containing between 0.1-15% by volume of H2, the remainder being composed of inert gas, H2O, O2, and unavoidable impurities, and having a dew point DP2 between -30°C and 0°C, the dew point DP1 being higher than the dew point DP2. Nitrogen can be used as the inert gas.

[0038] Atmospheres A1 and A2 can be achieved by using preheated steam and incorporating N2-H2 gas in a furnace equipped with pyrometers, H2 detectors and dew point detectors in different parts to monitor the H2, dew point and temperature of the atmosphere.

[0039] Cooling can be accomplished in an atmosphere containing 20-50% H2 along with N2. This gas mixture is blown onto the steel surface using a high speed fan. Cooling can also be accomplished by any other cooling means such as chill rolls.

[0040] In the following section, the physical phenomena in the heating and soaking process will be described to grasp the core of the present invention, without being bound by any theory.

[0041] During the heating process, the temperature gradually increases with a relatively high dew point, allowing for a high pO2 (oxygen partial pressure), leading to the diffusion of oxygen into the steel. This increase in oxygen diffusion has two major consequences. First, it allows for deep decarbonization of the subsurface layers of the steel by reaction with the interstitial carbon. Second, oxygen reacts with substitutional oxide-forming elements such as Mn, Si, Al and Cr to form internal oxides in the subsurface layers of the steel that reduce the amount of alloying elements available to form surface oxides. These internal oxides occur preferentially on the grain boundary regions due to the faster diffusion of these alloying elements.

[0042] At the end of the heating process the subsurface layer of the steel comprises: - a partially decarbonized layer having a thickness between 10 and 30 μm and a carbon weight percentage between 5 and 20 percent of the carbon weight percentage of the bulk steel; - A decarbonized layer that is outside the partially decarbonized layer, has a thickness between 30 and 70 μm, and has a carbon weight percentage that is less than 5 percent of the carbon weight percentage of the bulk steel.

[0043] These values ​​are given only for guidance: parameters such as the heating time, the temperature at the end of the heating, the carbon content of the steel and the dew point, which determines pO2, influence the thickness of the fully decarbonized layer as well as the partially decarbonized layer.

[0044] In the soaking process, the temperature is higher but the dew point is lower compared to the heating process, which has some effects on the subsurface layer of the steel.

[0045] Due to the relatively low dew point at the soaking zone, the amount of oxygen is also less and therefore diffuses to a limited (shallower) depth into the subsurface layer of the steel, which causes the decarburization reaction at the limited depth of the subsurface layer of the steel. Meanwhile, carbon atoms diffuse from the bulk into the carbon-depleted zone in the subsurface region of the steel (partially decarburized zone, followed by the decarburized zone). In fact, the carbon atoms present in the partially decarburized zone diffuse into the decarburized zone, which is refilled with carbon atoms from the bulk. This therefore produces a decarburized zone very close to the steel surface. The decarburization reaction depends on several factors such as soaking temperature, dew point (pO2), soaking time and the amount of carbon in the bulk steel.

[0046] As a result, at the end of the soaking step, the subsurface layer of the steel contains: - A partially decarbonized layer with a thickness of about 30 μm and a carbon weight percentage between 5 and 20% of the carbon weight percentage of the bulk steel. - A decarbonized layer that is outside the partially decarbonized layer, has a thickness of about 20 μm and has a carbon weight percentage that is less than 5 percent of the carbon weight percentage of the bulk steel.

[0047] These values ​​are given for guidance only.

[0048] Due to the higher oxygen partial pressure (pO2) in the heating zone, a larger amount of O2 can easily diffuse in the sub-surface layer of the steel and form internal oxides, thus trapping Si, Mn, Cr, and Al at a much deeper depth in the sub-surface layer. This phenomenon occurs in the early stage of recrystallization in the heating zone. In the soaking zone, grain growth and the formation of large ferrite grains mainly occur in the steel sub-surface layer.

[0049] The formation of internal oxides deeper in the subsurface region of the steel and subsequent grain growth resulted in the formation of an internal oxide-free ferrite layer on the steel surface, which can easily react with aluminum in the coating bath during galvanizing to form a satisfactory inhibition layer.

[0050] Contrary to the prior art, in this annealing treatment the dew point of the heating step is higher than that of the soaking step, making it possible to improve the properties of the steel in terms of liquid metal embrittlement (LME) resistance, as explained above. The invention also appears to have the advantage of producing a completely decarburized layer of controlled depth with a carbon weight percentage less than 5 percent of the carbon weight percentage of the bulk steel.

[0051] Preferably, the dew point DP2 is between -25°C and +10°C. Preferably, the dew point DP2 is between -20°C and 0°C. Preferably, the dew point DP2 is between -25°C and -5°C. Even more preferably, the dew point is between -25°C and -5°C.

[0052] Preferably, in the cooling step, the steel sheet is cooled to a temperature T3 between Ms and Ms+150°C and maintained at T3 for at least 40 seconds in an atmosphere A3 containing 1-30% by volume of H2 and inert gas and having a dew point DP3 of -40°C or less. More preferably, the temperature T3 is between Ms+10°C and Ms+150°C. This allows the steel sheet to have a carbon-enriched microstructure.

[0053] Preferably, after the cooling step iv), the steel sheet is cooled to a temperature T QT and then undergoes a reheating step v) in which the steel sheet is reheated to a temperature T4 between 300 and 550°C for a period between 30 and 300 seconds. Such a step is also known as a carbon enrichment step. Even more preferably, the steel sheet is optionally reheated to a temperature T4 between 300 and 550°C for a period between 2 and 8 seconds. QT Even more preferably, the steel plate is reheated to a temperature T4 between 330 and 490°C.

[0054] Preferably, after said cooling step iv) and said reheating step v), in an equalization step vi), said steel strip is heated at a temperature between 300°C and 500°C in an atmosphere A4 containing between 1 and 30% by volume of H2 and at least an inert gas and having a dew point DP4 below -40°C.

[0055] Preferably, the steel sheet of step A) has at least a weight percentage of 0.001≦Cr+Mo≦1.000%.

[0056] Preferably, said heating and soaking step lasts for 100 to 500 seconds. Preferably, in said heating and soaking step, the atmospheres A1 and A2 contain between 3 and 8% by volume of H2.

[0057] Preferably, DP1 is between 5 and 40° C. higher than DP2. Even more preferably, DP1 is between 10 and 30° C. higher than DP2.

[0058] Preferably, in step C), the coating is performed by electroplating or hot dip plating.

[0059] Preferably, in step C), the coating is performed by a hot dip galvanizing method, the steel strip having an aluminum content between 0.15 and 0.40% by weight, set at a temperature between 5 and 10°C higher than the galvanizing bath maintained at a temperature between 450 and 470°C.

[0060] Preferably, in step C), the coating is carried out by a hot-dip galvanizing method, the steel strip having an aluminum content between 0.09 and 0.15% by weight, set at a temperature 5 to 10° C. higher than a galvanizing bath maintained at a temperature between 450 and 470° C., and then heated after leaving the galvanizing bath to a temperature between 470 and 550° C. Such a treatment step makes it possible to produce a galvannealed steel strip.

[0061] Figures 5 and 6 show two typical thermal cycles. In Figure 5, the preheating of the full hard steel plate starts from room temperature and lasts for 146 seconds until the steel reaches 575°C. Then, during the heating step, the steel is heated from 575°C to 715°C in 131 seconds, and then from 715°C to the soaking temperature (800°C) in 174 seconds. The strip then goes through a soaking step, where the temperature is maintained at 800°C for 146 seconds. Finally, the strip is quenched to 190°C by quenching. The plate then goes through a reheating step, also known as the carbon enrichment step of the heat treatment, at 365°C for 105 seconds, and is cooled to 465°C. heating The steel is finally galvanized in a Zn-0.2 wt.% Al bath maintained at 460°C.

[0062] As shown in Figure 6, the preheating of the full hardened steel plate starts from room temperature and lasts for 146 seconds until the steel reaches 675°C. Then, during the heating process, the steel is heated from 675°C to 815°C in 131 seconds, and then from 815 to the soaking temperature (880°C) in 174 seconds. The strip then goes through a soaking process, where its temperature is maintained at 880°C and the soaking is performed for 146 seconds. Finally, the strip is quenched to 280°C by quenching. The strip then goes through a reheating stage, also known as the carbon enrichment stage of the heat treatment, at 450°C for 105 seconds, and then cooled to 460°C. heating The steel is finally galvanized in a Zn-0.2 wt.% Al bath maintained at 460°C.

[0063] As shown in FIG. 7, the present invention also relates to a galvanized steel strip produced as previously described and comprising: - steel bulk 18 having the composition described above, - on said steel bulk 18, a partially decarbonized layer 17 having a thickness between 20 and 40 μm, a carbon weight percentage between 5 and 20 percent of the carbon weight percentage of the bulk steel, and a microstructure comprising at least 50% ferrite and at least one of the following constituents: bainite, martensite and / or retained austenite, - on top of the partial decarbonization layer 17, a decarbonization layer 16 having a thickness between 5 and 40 μm, a carbon weight percentage less than 5 percent of the carbon weight percentage of the bulk steel, and a microstructure containing at least 90% ferrite, the upper part of the decarbonization layer 16 having a thickness between 2 and 12 μm and comprising an inner oxide layer (15) containing Mn, Si, Al and Cr based elemental oxides and mixed oxides of Mn, Si, Al and Cr, - on said inner oxide layer 15, a blocking layer 14 having a thickness between 100 nm and 500 nm, on said blocking layer 14 a zinc-based coating layer 13 having a thickness between 3 μm and 30 μm.

[0064] The inner oxide layer is outside the decarbonized layer and closer to the inhibition layer, as shown in Figure 7. The inner oxide layer includes the oxide, has a carbon weight percent less than 5 percent of the carbon weight percent of the bulk steel, and has at least 90 percent ferrite.

[0065] As shown in FIG. 8, the present invention also relates to a galvannealed steel strip produced as previously described and comprising: - steel bulk 18 having the composition described above, - on said steel bulk 18, a partially decarbonized layer 17 having a thickness between 20 and 40 μm, a carbon weight percentage between 5 and 20 percent of the carbon weight percentage of the bulk steel, and a microstructure comprising at least 50% ferrite and at least one of the following constituents: bainite, martensite and / or retained austenite, - on the outside of the partial decarbonization layer 17, a decarbonization layer 16 having a thickness between 5 and 40 μm, a carbon weight percentage less than 5 percent of the carbon weight percentage of the bulk steel, and a microstructure containing at least 90% ferrite, the upper part of the decarbonization layer 16 having a thickness between 2 and 12 μm and comprising an inner oxide layer (15) containing Mn, Si, Al and Cr based elemental oxides and mixed oxides of Mn, Si, Al and Cr, on said inner oxide layer 15, a zinc-based coating layer 12 having a thickness between 3 and 30 μm and containing between 10 and 20 weight percent iron.

[0066] The inner oxide layer cannot be thicker than the decarburized layer. As a result, if the thickness of the decarburized layer is "x" μm, where x is between 5 and 12 μm, the thickness of the inner oxide layer is between 2 and "x". The inner oxide layer is outside the decarburized layer and close to the blocking layer, as shown in FIG. 8. The inner oxide layer includes the oxides, has a carbon weight percent less than 5 percent of the carbon weight percent of the bulk steel, and has at least 90% ferrite.

[0067] The steel strip preferably has a thickness between 0.5 mm and 3.0 mm.

[0068] The steel strip preferably has an ultimate tensile strength (UTS) of greater than 900 MPa.

[0069] The present invention also relates to a spot welded joint of two metal sheets, including at least one steel sheet as described above, which joint is free of cracks having a size exceeding 100 μm.

[0070] The spot welded joint preferably includes two or three metal plates. The spot welded joint preferably also includes an aluminum plate or a steel plate.

[0071] The invention also relates to the use of any coated steel sheet as described above or any spot welded joint as described above for the manufacture of motor vehicles. EXAMPLES

[0072] The following sections present experimental results showing the improved surface and subsurface properties. The experiments were carried out on two different steel grades (Steel A and Steel B) with strip thicknesses between 1.4 and 1.6 mm.

[0073] The different experimental parameters are reported in Table 1.

[0074] The first set of experiments (A1 and A2 * ) was carried out to show the effect of different dew points in the heating zone and soaking zone on the decarbonization behavior of the steel for the first steel type (Steel A). The steel was annealed and then galvanized in a Zn-0.20 wt% Al coating bath according to the thermal cycle reported in Fig. 5. As a result, the thermal cycles of both experiments are similar. In experiment A1, almost the same dew points were maintained in the heating zone (-5°C) and soaking zone (-3°C), while in experiment A2, * In this experiment, a higher dew point was applied in the heating zone (-1°C) compared to the soaking zone (-9°C). In both experiments, the hydrogen concentration was maintained between 4 and 5% in both zones.

[0075] The second experiment (A3 * ) was carried out on steel A. After annealing the steel was galvanized in a Zn-0.129 wt% Al coating bath according to the thermal cycle reported in Fig. 5. Immediately after galvanization, a post-coating heat treatment, also known as galvannealed hot-dip galvanizing, was carried out at 480 °C. In this experiment, a higher dew point was also applied in the heated zone (0 °C) compared to the soaked zone (-10 °C), maintaining about 5% hydrogen in both zones.

[0076] The third experiment (B1 * ) was performed on another steel type (Steel B). The steel was annealed and then galvanized in a Zn-0.20 wt% Al coating bath according to the thermal cycle reported in Figure 6. The peak annealing temperature is higher for Steel B compared to Steel A. In this experiment, a higher dew point was also applied in the heating zone (-5°C) compared to the soaking zone (-20°C), maintaining about 5% hydrogen in both zones.

[0077] Fourth experiment (B2 * ) was also performed on steel B. After annealing the steel was galvanized in a Zn-0.129 wt% Al coating bath according to the thermal cycle reported in Figure 6. Immediately after galvanization, a post-coating heat treatment, also known as galvannealed hot-dip galvanizing, was performed at 510 °C. In this experiment, a higher dew point was also applied in the heated zone (+4 °C) compared to the soak zone (-5 °C), maintaining about 5% hydrogen in both zones.

[0078] Test A2 * , A3 * , B1 * and B2 * According to the present invention, the dew point of the heating section is higher than the dew point of the soaking section.

[0079] [Table 1]

[0080] <Decarbonized layer> FIG. 9 shows the results of experiments A1 (left photo) and A2 using steel A. * The photographs on the right side show a comparison of SEM micrographs of the decarbonized layer formed on the near-surface of steel produced according to the method described above.

[0081] Micrograph A2* of the subsurface region of the steel of the invention shows: - Steel Bulk 18, - a partially decarbonized layer 17 of about 30 μm, whose carbon weight percentage is between 5 and 20 percent of the carbon weight percentage of the bulk steel; - A decarbonized layer 16 of about 20 μm, the carbon weight percentage of which is less than 5 percent of the carbon weight percentage of the bulk steel.

[0082] In contrast, the micrograph A1 of the subsurface layer of the steel according to the prior art shows only the bulk 18 of the steel and a partial decarburized layer 17 of about 45 μm. This comparison shows the advantage of the claimed method regarding the formation of a decarburized layer in the subsurface region of the steel, which is preferred for obtaining targeted mechanical properties as well as liquid metal embrittlement resistance properties.

[0083] Figure 10 shows the results of experiments A1 (left photo) and A2. * An SEM micrograph of a sample of Steel A produced through (right photo) shows the presence of an inner oxide 15, an inhibition layer 14 and a galvanized coating 13.

[0084] FIG. 11 shows the results of experiment B1. * 3 shows two SEM micrographs of a sample of Steel B produced through 3. A micrograph of the subsurface layer of the steel is presented below. - Steel Bulk 18, - a partially decarbonized layer 17 of about 30 μm, whose carbon weight percentage is between 5 and 20 percent of the carbon weight percentage of the bulk steel; - a decarbonized layer 16 of about 15 μm, the carbon weight percentage of which is less than 5 percent of the carbon weight percentage of the bulk steel; an inhibition layer 14, an inner oxide layer 15 and a galvanized coating layer 13.

[0085] Figure 12 shows the results of experiment A3. * 3 shows two SEM micrographs of a sample of Steel A produced through 3. A micrograph of the subsurface layer of the steel shows: - Steel Bulk 18, - a partially decarbonized layer 17 of about 30 μm, whose carbon weight percentage is between 5 and 20 percent of the carbon weight percentage of the bulk steel; - A decarbonized layer 16 of about 20 μm, the carbon weight percentage of which is less than 5 percent of the carbon weight percentage of the bulk steel. This experiment shows that the preferred claimed method is that DP1 is between 5°C and 30°C higher than DP2.

[0086] Figure 13 shows the results of experiment B2. * 1 shows two SEM micrographs of a sample of Steel B produced through. The left micrograph of the subsurface layer of the steel shows: - Steel Bulk 18, - a partially decarbonized layer 17 of about 30 μm, whose carbon weight percentage is between 5 and 20 percent of the carbon weight percentage of the bulk steel; - A decarbonized layer 16 of about 15 μm, the carbon weight percentage of which is less than 5 percent of the carbon weight percentage of the bulk steel.

[0087] <Zinc plating and galvannealed hot-dip coating> Test A2 * Figures 9 and 10 show the results for Experiment B1. *The claimed method produces a surface suitable for reactive wetting during galvanization, as shown for Fig. 11. The Zn-0.20 wt% Al bath composition was maintained during galvanization of Steel A and Steel B, as reported in Table 1. During galvanization, a continuous inhibition layer developed at the steel / coating interface indicating good reactive wetting behavior.

[0088] Test A3 * and B2 * In the present study, galvannealed coated steels A and B were produced by galvanizing in a Zn-0.129 wt.% Al bath followed by post-coating heat treatment (also known as galvannealed coating) at 480°C for Steel A and 510°C for Steel B, respectively. Figures 12 and 13 show cross-sectional SEM micrographs of galvannealed coated steels A and B, respectively. These micrographs show that the claimed method is suitable for producing galvannealed coated steels.

[0089] <Evaluation of resistance to liquid metal embrittlement> The liquid metal embrittlement (LME) susceptibility of the above galvanized and galvannealed coated steels produced according to the thermal cycle reported in Table 1 was evaluated using the A2 * , A3 * , B1 * and B2 * The steels produced under the experimental conditions were evaluated by resistance spot welding. The electrode type was ISO type B with a face diameter of 6 mm, the electrode force was 5 kN, and the water flow rate was 1.5 g / min. The welding cycle is reported in Table 2.

[0090] [Table 2]

[0091] The LME crack resistance behavior was evaluated using the three-layer stack condition. In this condition, three coated steel sheets were welded together by resistance spot welding as shown in FIG. 14, which shows the joint surfaces of the indentation area 19, the area deformed by the indentation 20, the heat affected zone (HAZ) area 21, the HAZ / weld nugget interface area 22 and the HAZ area 23. All resistance spot welding tests were performed including severe noise factors, such as the gap 24 between the two steel sheets, the offset 25 between the welding electrode and the steel sheets, the electrode angle 26 between the welding electrode and the steel sheets, etc., as shown in FIG. 15. The number of cracks larger than 100 μm was then evaluated using an optical microscope as shown in Table 3 in all five locations as shown in FIG. 14. The excellent LME resistance behavior was observed in a wide range of steel sheet thicknesses without welding noise factors due to the presence of a specific thickness of the decarbonized layer.

[0092] [Table 3]

Claims

1. A method for producing a coated steel sheet coated with a zinc-based coating, comprising the steps of: A) Preparation of a steel sheet having the following chemical composition in weight percent: 0.01≦Al≦1.0%, 0.07≦C≦0.50%, 0.3≦Mn≦5.0%, V<0.2%, 0.01≦Si≦2.45%, 0.35≦Si+Al≦3.5, N≦0.01%, P≦0.04%, S≦0.01%, and optionally at least one of the following elements in weight percent: B≦0.004%, Co≦0.1%, Cu≦0.5%, 0.001≦Cr≦1.00%, 0.001%≦Mo≦0.5%, Nb≦0.1%, Ni≦1.0%, Ti≦0.1%, with the remainder of the composition being iron and unavoidable impurities resulting from refining, B) Annealing of a steel sheet comprising, in this order: i) Temperature T between room temperature and 550° C. to Ac1+50° C. 1 a preheating step of heating the steel sheet to ii) between 0.1 and 15% by volume H 2 The balance is an inert gas, H 2 O, O 2 and unavoidable impurities, with a dew point DP between -10°C and +30°C 1 At temperature T 1 Recrystallization temperature T between 720°C and 1000°C 2 a heating step of heating the steel sheet to iii) between 0.1 and 15% by volume H 2 The balance is an inert gas, H 2 O, O 2 and unavoidable impurities, with a dew point DP between -30°C and 0°C 2 and the dew point DP 1 is the dew point DP 2 Recrystallization temperature T in higher atmosphere A2 2 a heat soaking step of holding the steel sheet in iv) The steel plate is heated to a temperature T between (Ms-5°C) and (Ms-170°C). QT a cooling step of cooling the C) coating said steel sheet with a zinc-based coating; Including, The coated steel sheet is - a steel bulk (18) having the composition previously described, - on said steel bulk (18), a partially decarburized layer (17) having a thickness between 20 and 40 μm, a carbon weight percentage between 5 and 20 percent of the carbon weight percentage of the bulk steel, and a microstructure comprising at least 50% ferrite and at least one of the following constituents: bainite, martensite and / or retained austenite, - on said partially decarbonized layer (17), a decarbonized layer (16) having a thickness between 5 and 40 μm, a carbon weight percentage less than 5 percent of the carbon weight percentage of the bulk steel, and a microstructure containing at least 90% ferrite, the upper part of said decarbonized layer (16) having a thickness between 2 and 12 μm and comprising an inner oxide layer (15) containing Mn, Si, Al and Cr-based elemental oxides and mixed oxides of Mn, Si, Al and Cr, - on said inner oxide layer (15), a blocking layer (14) having a thickness between 100 nm and 500 nm; - on said blocking layer (14), a zinc-based coating layer (13) having a thickness of 3 to 30 μm, Including, method.

2. After the cooling step iv), in the carbon enrichment step v), the steel sheet is heated to a temperature T 4 The method of claim 1 wherein the mixture is reheated to

3. In the carbon enrichment step v), the steel strip is enriched with between 1 and 30% by volume of H 2 and at least an inert gas, 4 3. The method according to claim 2, wherein the substrate is heated to a temperature between 300° C. and 500° C. in an atmosphere A4 where the temperature is −40° C. or lower.

4. In the ii) heating step and the iii) soaking step, DP 1 is DP 2 The method according to any one of claims 1 to 3, wherein the temperature is between 5 and 40°C higher than

5. D.P. 1 is DP 2 The method of claim 4, wherein the temperature is between 10 and 30° C. higher than the

6. 6. The method according to any one of claims 1 to 5, wherein in step C) the coating is performed by a hot dip galvanizing method, the steel strip having an aluminium content between 0.15 and 0.40% by weight, set at a temperature between 5 and 10 °C higher than a galvanizing bath maintained at a temperature between 450 and 470 °C.

7. In step C), the coating is carried out by a hot dip galvanizing method, the steel strip having an aluminum content between 0.09 and 0.15% by weight, set at a temperature 5 to 10° C. higher than a galvanizing bath maintained at a temperature between 450 and 470° C. and then heated to a temperature between 470 and 550° C. after leaving the galvanizing bath, The coated steel sheet is - a steel bulk (18) having a composition as defined in claim 1, - on said steel bulk (18), a partially decarburized layer (17) having a thickness between 20 and 40 μm, a carbon weight percentage between 5 and 20 percent of the carbon weight percentage of the bulk steel, and a microstructure comprising at least 50% ferrite and at least one of the following constituents: bainite, martensite and / or retained austenite, - on the outside of said partial decarburization layer (17), a decarburization layer (16) having a thickness between 5 and 40 μm, a carbon weight percentage less than 5 percent of the carbon weight percentage of the bulk steel, and having a microstructure containing at least 90% ferrite, the upper part of said decarburization layer (16) having a thickness between 2 and 12 μm and comprising an inner oxide layer (15) containing Mn, Si, Al and Cr-based elemental oxides and mixed oxides of Mn, Si, Al and Cr, - on said inner oxide layer (15), an iron-zinc based coating layer (12) having a thickness between 3 μm and 30 μm and containing 10 to 20 weight percent iron; Including, The method according to any one of claims 1 to 5.

8. Produced according to any one of claims 1 to 6, comprising: - a steel bulk (18) having the composition previously described, - on said steel bulk (18), a partially decarburized layer (17) having a thickness between 20 and 40 μm, a carbon weight percentage between 5 and 20 percent of the carbon weight percentage of the bulk steel, and a microstructure comprising at least 50% ferrite and at least one of the following constituents: bainite, martensite and / or retained austenite, - on said partially decarbonized layer (17), a decarbonized layer (16) having a thickness between 5 and 40 μm, a carbon weight percentage less than 5 percent of the carbon weight percentage of the bulk steel, and a microstructure containing at least 90% ferrite, the upper part of said decarbonized layer (16) having a thickness between 2 and 12 μm and comprising an inner oxide layer (15) containing Mn, Si, Al and Cr-based elemental oxides and mixed oxides of Mn, Si, Al and Cr, - on said inner oxide layer (15), a blocking layer (14) having a thickness between 100 nm and 500 nm; - on said blocking layer (14), a zinc-based coating layer (13) having a thickness of 3 to 30 μm, Hot-dip galvanized steel strip including.

9. Manufactured according to claim 7, comprising: - a steel bulk (18) having the composition previously described, - on said steel bulk (18), a partially decarburized layer (17) having a thickness between 20 and 40 μm, a carbon weight percentage between 5 and 20 percent of the carbon weight percentage of the bulk steel, and a microstructure comprising at least 50% ferrite and at least one of the following constituents: bainite, martensite and / or retained austenite, - on the outside of said partial decarburization layer (17), a decarburization layer (16) having a thickness between 5 and 40 μm, a carbon weight percentage less than 5 percent of the carbon weight percentage of the bulk steel, and having a microstructure containing at least 90% ferrite, the upper part of said decarburization layer (16) having a thickness between 2 and 12 μm and comprising an inner oxide layer (15) containing Mn, Si, Al and Cr-based elemental oxides and mixed oxides of Mn, Si, Al and Cr, - on said inner oxide layer (15), an iron-zinc based coating layer (12) having a thickness between 3 μm and 30 μm and containing 10 to 20 weight percent iron; Including, hot-dip galvanized steel strip.

10. A steel strip according to claim 8 or 9, having a thickness between 0.5 mm and 3.0 mm.

11. 11. A steel strip according to claim 8 or 10, having an ultimate tensile strength of more than 900 MPa.

12. A spot welded joint of at least two metal sheets, including at least one steel sheet according to any one of claims 9 to 11, the spot welded joint being free of cracks having a size exceeding 100 μm.

13. Use of the coated steel sheet according to any one of claims 9 to 11 or the spot welded joint according to claim 12 for the manufacture of motor vehicles.

Citation Information

Patent Citations

  • High-strength hot-dip galvanized steel plate and method for manufacturing the same

    JP2011219778A

  • Method for manufacturing steel sheet products with a metal protective layer formed by hot-dip plating.

    JP2014525986A

  • High strength hot-dip galvanized steel sheet and method for producing the same

    JP2015151605A

  • Cold-rolled steel sheet, manufacturing method, and vehicle

    JP2016529392A